Analog Design Centering and Sizing - Graeb, Helmut E. (Springer Netherlands : Imprint: Springer, 2007)
This book represents a compendium of fundamental problem formulations of analog design centering and sizing. It provides a differentiated knowledge about the tasks of analog design centering and sizing. In particular the worst-case problem will be formulated. It stands at the interface between process technology and design technology. Analog Design Centering and Sizing wants to point out that and how both process and design technology are required for its solution. The intention is to enable analog and mixed-signal designers to assess CAD solution methods that are presented to them. On the other side, the intention is to enable developers of analog CAD tools to formulate and develop solution approaches for analog design centering and sizing. The structure of Analog Design Centering and Sizing is geared towards a combination of a reference book and a textbook. The formulations of tasks and solution approaches by mathematical means makes the book suitable as well for students dealing with analog design and design methodology.